The Philosophy of Thomas Hobbes: Monist, Materialist and Mechanist - Machamer, Peter (Hybris, 2012)
This essay will present Hobbes as the most consistent philosopher of the 17th century, and show that in all areas his endeavors have cogency that is unrivalled, in many ways even to this day. The second section will outline Hobbes’ conception of philosophy and his causal materialism. Section 3 will deal briefly with Hobbes’ discussion of sensation and then present his views on the nature and function of language and how reason depends upon language. Section 4 portrays his views about the material world; Section 5 deals with nature of man; and the 6th section with the artificial body of the commonwealth and the means of its creation.